Demographic characteristics, site and phylogenetic distribution of dogs with appendicular osteosarcoma: 744 dogs (2000-2015). - Joanne L Tuohy; Marejka H Shaevitz; Laura D Garrett; Audrey Ruple; Laura E Selmic (PLoS ONE)
Objective To report demographic characteristics of a contemporary population of dogs with appendicular osteosarcoma and assess the relationship between demographic characteristics, site distribution, and phylogenetic breed clusters. Design Retrospective case series. Methods A search of the Veterinary Medical Database was performed for dogs with appendicular osteosarcoma as a new diagnosis. Entries were reviewed for the sex, neuter status, age at diagnosis, breed, affected limb, and tumor location. The reported breed for purebred dogs was used to categorize each dog into one of five phylogenetic groups based on microsatellite analysis. Results 744 client-owned dogs were included in the study. Study dogs were represented by a male-to-female ratio of 0.95:1.0, the majority of which (80.9%) were neutered. Most dogs were diagnosed between 7-10 years of age. The majority (77.8%) of dogs were large or giant-breed dogs. Purebred dogs comprised 80.4% of the population. The most common purebred breed affected by OS was the Rottweiler (17.1%). The most common phylogenetic group represented was Mastiff-Terrier (M-T, 26.3%). OS was more commonly located in the forelimb (64.2%) versus the hindlimb (35.8%), and the humerus was the most common site (20.9%). The distribution of age groups and tumor locations were significantly different between phylogenetic clusters. The distribution of age groups and neuter status were significantly different between size groups. Conclusions and significance The demographic data of canine appendicular OS are similar to previous reports. The data on phylogenetic associations can guide future studies aimed at evaluating the genomic mutations that contribute to OS development and its biological behavior.